2000
DOI: 10.1097/00000421-200010000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Profile of Patients With Advanced Cancer Before and After Taxane Treatment

Abstract: The purpose of this study is to determine immune recovery and function after treatment with docetaxel or paclitaxel. Peripheral blood mononuclear cells were harvested before chemotherapy and at weekly times afterwards for cycle 1. Leukocyte subsets ICD45hiCD14lo polymorphonuclear neutrophils, CD45hiCD14hi monocytes, CD45hiCD14- lymphocytes, CD3+CD4/CD8+ T cells, CD3-CD19+ B cells, CD3-CD16/CD56+ natural killer (NK) cells], and circulating cytokine levels [tumor necrosis factor-alpha, gamma-interferon (gamma-IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…The most commonly documented immune response in patients receiving paclitaxel is the development of myelosuppression in the weeks after the administration of this cytotoxic agent (21). However, an analysis of leukocyte subsets in patients receiving taxane therapy revealed no alterations in T-cell or B-cell frequency or CD4: CD8 ratio (9). Other reports purporting a stimulatory effect of paclitaxel have focused on its ability to activate immune effectors such as monocytes/macrophages that have receptors for lipopolysaccharides and other foreign compounds that can cross-react with the paclitaxel molecule (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly documented immune response in patients receiving paclitaxel is the development of myelosuppression in the weeks after the administration of this cytotoxic agent (21). However, an analysis of leukocyte subsets in patients receiving taxane therapy revealed no alterations in T-cell or B-cell frequency or CD4: CD8 ratio (9). Other reports purporting a stimulatory effect of paclitaxel have focused on its ability to activate immune effectors such as monocytes/macrophages that have receptors for lipopolysaccharides and other foreign compounds that can cross-react with the paclitaxel molecule (22).…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al (9) studied lymphocyte subsets, levels of circulating cytokines, T-cell mitogenic function, and NK cell function in 10 patients with advanced cancer who received paclitaxel or docetaxel. They found that patients exhibiting a partial or complete response to therapy demonstrated higher than normal CD4:CD8 T-cell ratios and increased T-cell proliferation in response to phytohemagglutinin (PHA) at 4 weeks posttreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Taxanes are immunostimulatory against neoplasms, supporting the idea that these agents suppress cancer through several mechanisms and not solely through inhibiting cell division (Lee et al, 2000a;Tong et al, 2000). Immune function was affected more significantly after docetaxel treatment (Chan and Yang, 2000).…”
mentioning
confidence: 90%
“…However, the actions of these drugs on Bcl-2 and on the mitochondria might be expected to be non-selective and affect all cells. Indeed paclitaxel treatment is associated with serious side effects, including neuropathy (12) and low white blood cell counts (13). These side effects occur rapidly, appear to be due to drug action on terminally differentiated cells, and are slowly reversible.…”
mentioning
confidence: 99%